Conclusion: Young Leaders in Mission - Franco, Edna P (Archīum Ateneo, 2023)
Starting in 2012; several young Ateneo graduates have engaged with each other; under the mentorship of Fr. Bienvenido F. Nebres; in sessions they called "#Leadership With Fr Ben" as they become a new generation of leaders working for and with the poor. They bring us into the world of the majority poor in our country. Blending faith and social involvement; faith and justice; marks the life and journey of the young leaders in this book. This concluding chapter synthesizes the quest for good leadership and the fertile soil; systems thinking; and community collaboration that makes it possible.